(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
A syringe pump project entails the design or assembly of a device specifically engineered for the accurate administration of liquids, frequently utilized in both medical and research environments. Essential components generally consist of a syringe, a motor, a control interface, and a power supply. This device enables precise control over dosage and timing, thereby enhancing the delivery of medications and the execution of biological experiments with exceptional accuracy. Opportunities for enhancement may include the development of user-friendly interfaces, remote control functionalities, and integration with advanced technologies such as artificial intelligence or machine learning. Although there are some limitations, including noise production and challenges in returning to the zero-point, syringe pumps continue to be indispensable instruments for fulfilling their intended purposes in healthcare and scientific inquiry.